Characteristics of Syngas Auto-ignition at High Pressure and Low Temperature Conditions with Thermal Inhomogeneities. (2015) - Pal, Pinaki; Mansfield, Andrew B.; Wooldridge, Margaret S.; Im, Hong G.
Abstract: Effects of thermal inhomogeneities on syngas auto-ignition at high-pressure low-temperature conditions, relevant to gas turbine operation, are investigated using detailed one-dimensional numerical simulations. Parametric tests are carried out for a range of thermodynamic conditions ( T = 890-1100 K, P = 3-20 atm) and composition ( Ф = 0.1, 0.5). Effects of global thermal gradients and localized thermal hot spots are studied. In the presence of a thermal gradient, the propagating reaction front transitions from spontaneous ignition to deflagration mode as the initial mean temperature decreases. The critical mean temperature separating the two distinct auto-ignition modes is computed using a predictive criterion and found to be consistent with front speed and Damkohler number analyses. The hot spot study reveals that compression heating of end-gas mixture by the propagating front is more pronounced at lower mean temperatures, significantly advancing the ignition delay. Moreover, the compression heating effect is dependent on the domain size.